2002
DOI: 10.1007/s00204-001-0304-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and genotoxic effects of fumonisin B1 on rabbit kidney RK13 cell line

Abstract: Fumonisins, mycotoxins produced by certain strains of Fusarium moniliforme, could induce various diseases in animals and are suspected human carcinogens. Fumonisin B1 (FB1), the most commonly found fumonisin, has been characterised as a tumour initiator and a tumour promoter, a mitogen and an anti-proliferative agent. In this study we examined the cytotoxicity and genotoxicity of FB1 in rabbit kidney RK13 cells. To evaluate the effects of FB1 on survival of this cell line we analysed cell viability, membrane i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Related to this, Norred et al (1992) reported that FB 1 could not be considered to be a genotoxic mycotoxin, when evaluated by its ability to induce unscheduled DNA synthesis (UDS) in primary rat hepatocytes. However, genetic damage was observed by other authors when the toxin was tested by its ability to induce MN in primary hepatocytes (Knasmuller et al, 1997), rabbit kidney RK13 cells (Rumora et al, 2002), human lymphocytes and Allium cepa (onion) (Lerda et al, 2005). Moreover, the FB 1 was also found to be genotoxic in vitro when it was evaluated by means of comet assay in rat astrocytes (Galvano et al, 2002a) and in human fibroblasts (Galvano et al, 2002b).…”
Section: Discussionmentioning
confidence: 87%
“…Related to this, Norred et al (1992) reported that FB 1 could not be considered to be a genotoxic mycotoxin, when evaluated by its ability to induce unscheduled DNA synthesis (UDS) in primary rat hepatocytes. However, genetic damage was observed by other authors when the toxin was tested by its ability to induce MN in primary hepatocytes (Knasmuller et al, 1997), rabbit kidney RK13 cells (Rumora et al, 2002), human lymphocytes and Allium cepa (onion) (Lerda et al, 2005). Moreover, the FB 1 was also found to be genotoxic in vitro when it was evaluated by means of comet assay in rat astrocytes (Galvano et al, 2002a) and in human fibroblasts (Galvano et al, 2002b).…”
Section: Discussionmentioning
confidence: 87%
“…Cell culture systems provide a good model for the evaluation of cytotoxicity of various compounds. We, therefore, employed the extensively used in vitro cell culture techniques of the proximal (LLC-PK1) and distal tubule (MDBK) cells [5][6][7] to study FTE-induced renal effects. The technique mimics the in vivo state, as these cell lines maintain similar biochemical function of levels of marker enzymes exhibited by freshly isolated cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cell lines used in this study were also used as model systems for testing of various xenobiotics, e.g. WBF344 for food and perfume additives 13 , RK13 for mycotoxins 14 , and the cell line Sf21 for testing of insect cell extracts 15 or novel insecticides 16 . Manji and Friesen 17 and Tseng et al 18 studied induction of apoptosis and Takahashi et al 19 cell cycle arrest induced by radiation in SF21 cell line.…”
Section: Discussionmentioning
confidence: 99%